IMPLEMENTING OF NUMBERED HEAD TOGETHER TEACHING READING COMPRHENSION IN JUNIOR HIGH SCHOOL - Ni Putu Ayu Tiah Mutiara Sari; Ida Ayu Sri Widiastuti; I Gede Putu Agus Pramerta (Academic Journal on English Studies (AJOES), 2023)
Reading comprehension is the ability to process written text, understand its meaning, and to integrate with what the reader already knows. This research aims to determine the effectiveness of the Numbered Head Together technique in improving reading comprehension, where the application is carried out in two cycles. The subjects of this research were the seventh-grade students at SMPN 5 Mengwi in academic year 2023/2024. The class consisted of 33 students who were deficient in reading, especially in reading comprehension. The data were then analyzed by comparing the results of the pre-test and post-tests which showed there were significant improvements of the subjects' mean score from the pre-test to post-tests. As the supporting data, the questionnaire was also administered at the end of the last cycle and the results showed positive responses on the implementation of Numbered Head Together. Based on the results of the research instruments, it could be concluded that Reading comprehension of the seventh-grade students of SMPN 5 Mengwi in academic year 2023/2024 could be improved through Numbered Head Together.